Hard News Revisited: A Case Study of Various Approaches to an Incident at a Primary School as Reflected in the Media - Panasenko, Nataliya; Krajčovič, Peter; Stashko, Halyna (Communication Today, 2021)
The study highlights various approaches to an incident at a primary school as reflected in the media. The authors analyze different media outputs and by using numerous examples prove the most important features of the news. They supplement their quantitative analysis with a qualitative analysis of the media outputs of selected news portals and focus on several key elements: title of the media output, content of the article, and signals of addressee orientation in the texts. The analysis is based on the comparison of the time of publication of the media output, the method of processing information and the headlines. Additionally, the study gives valuable information on the meaning of timeliness, conflict, proximity, and surprise. The research presents an exhaustive analysis of different forms of hard news production, forms of its reproduction, and media channels dividing media sources into three groups: news presented in serious portals, official sources, and tabloid news portals. Such an approach gives the opportunity to specify signals of addressee orientation in the headlines and the text body, typical of each media group. The results of the analysis vividly show what common and specific signals of addressee orientations in media sources, forming three groups – official, serious, and tabloids present hard news on their portals.